2020
DOI: 10.1016/j.ophtha.2019.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Deep Learning Models for Screening Multiple Abnormal Findings in Retinal Fundus Images

Abstract: Purpose: To develop and evaluate deep learning models that screen multiple abnormal findings in retinal fundus images. Design: Cross-sectional study. Participants: For the development and testing of deep learning models, 309 786 readings from 103 262 images were used. Two additional external datasets (the Indian Diabetic Retinopathy Image Dataset and e-ophtha) were used for testing. A third external dataset (Messidor) was used for comparison of the models with human experts. Methods: Macula-centered retinal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 33 publications
1
118
0
1
Order By: Relevance
“…Dataset Organisation. We used the retinal fundus images from the Seoul National University Bundang Hospital Retina Image Archive (SBRIA) after de-identification except the age, sex, and underlying diseases at the study date; details are described in our previous study 26,30 . We included 412,026 retinal fundus images from 155,449 participants obtained at the health promotion centre in Seoul National University Bundang Hospital (SNUBH) between June 1st, 2003, and June 30th, 2016, in which detailed information regarding the presence of hypertension, DM, and the smoking status was presented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dataset Organisation. We used the retinal fundus images from the Seoul National University Bundang Hospital Retina Image Archive (SBRIA) after de-identification except the age, sex, and underlying diseases at the study date; details are described in our previous study 26,30 . We included 412,026 retinal fundus images from 155,449 participants obtained at the health promotion centre in Seoul National University Bundang Hospital (SNUBH) between June 1st, 2003, and June 30th, 2016, in which detailed information regarding the presence of hypertension, DM, and the smoking status was presented.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, as retinal fundus images provide high-resolution in-vivo images of retinal vessels and parenchyma without any invasive procedure 15 , retinal fundus images have been used to detect target organ damage in vascular diseases (e.g., hypertension and diabetes mellitus [DM]), to screen retinal and optic disc diseases (e.g., age-related macular degeneration and glaucoma), and to predict cerebral/cardiovascular diseases [16][17][18][19][20][21] . Recently, deep neural networks have revolutionised the field of medical image analysis including retinal fundus images; deep-learning algorithms presented discriminative performances comparable to those of an ophthalmologist in diagnosing diabetic retinopathy, age-related macular degeneration, and glaucoma, as well as in predicting age, sex, and presence of cardiovascular diseases [22][23][24][25][26] . Previous study reported highly accurate results of a mean absolute error of 3.26 years for age prediction and receiver operating characteristic curve (AUC) of 0.97 for gender prediction 25 , however, there were several limitations including a low proportion of Asian, a lack of analysis of the differences in accuracy with age, and a lack of discussion of which parts of the fundus image were used for age prediction.…”
mentioning
confidence: 99%
“…Second, although DL systems developed based on traditional fundus images showed reliable performance for the detection of retinopathies, missed diagnoses were inevitable due to the limited visible scope of these fundus images. 16,26 Our study developed a robust DL model for detecting RH based on UWF images, the visible scope of which was five times larger than that of traditional fundus images. Thus, our system minimizes missed diagnoses of RH.…”
Section: Discussionmentioning
confidence: 99%
“…Fundus imaging allows the identification of the main ocular structures, such as the optic disc (OD), optic disc cup (OD-cup), macula region [12], fovea, [13] and blood vessels [14]. This test may also detect abnormal conditions, including microaneurysms, bleeding, exudates, and cotton wool spots [15].…”
Section: Introductionmentioning
confidence: 99%